The art of hearing heartbeats : a novel - Sendker, Jan-Philipp (Other Press, 2012)
When a successful New York lawyer suddenly disappears without a trace, neither his wife nor his daughter Julia has any idea where he might be--until they find a love letter he wrote many years ago to a Burmese woman they have never heard of. Intent on solving the mystery and coming to terms with her father's past, Julia decides to travel to the village where the woman lived. There she uncovers a tale of unimaginable hardship, resilience, and passion that will reaffirm the listener's belief in the power of love to move mountains.